Kilogram synthesis of pinoxaden. (13th September 2022) - Jiang, Shun; Zhao, Zhiwei; Yin, Lingfeng; Wang, Han; Mao, Yongjun
Abstract: An optimized kilogram‐scale synthetic route for pinoxaden was successfully developed. The key intermediate dimethyl 2‐(2, 6‐diethyl‐4‐methylphenyl)malonate (19 ) was prepared from 2, 6‐diethyl‐4‐methylaniline through diazotization reaction, Suzuki cross‐coupling reaction, and alcoholysis reaction in 59% yield over three steps in 97.3% purity. 1, 4, 5‐Oxadiazepane dihydrobromide (11 ) was obtained from diethylene glycol through esterification, cyclization, deprotection, and salification in 64% yield over three steps. Pinoxaden was given by aminolysis of 19 with 11, followed by acylation by pivaloyl chloride in 64% yield over two steps in 99.9% purity. Purification methods for the intermediates and the final product were developed. Abstract : Graphical Abstract of Pinoxaden.